THE USE OF KAHOOT GAMES APPLICATION TO IMPROVE VOCABULARY MASTERY OF THE EIGHTH GRADE STUDENTS AT SMP NEGERI 32 SIGI - Belinda, Belinda; Mukrim, Mukrim; Wahyudin, Wahyudin; Mocthar, Mochtar (Tadulako University, 2025)
The research aimed to find out the improvement of the students‘ vocabulary mastery by using kahoot games applications that focused on verbs and nouns. The research applied pre-experimental design with one group pre-test and post-test. The sample of the research was the eighth grade students at SMP Negeri 32 Sigi in academic year 2023/2024 which consisted of 29 students. The researcher used verbs and nouns of vocabulary test as instruments in pre-test and post-test. The research findings indicated that kahoot games application can improve students‘ vocabulary mastery. It was proved by the mean score of pre-test was 58.86 it classified as fair, post-test was 73.34, it classified as good and the improvement from pre-test to post-test was 24.60. Therefore there was the improvement of the students‘ vocabulary mastery. The result of improvement is also proved with t-test value. The researcher found that the value of t-test (7.352) was greater than t-table (2.048). This value means that there is a significant difference between the result of the students‘ pre-test and post test. The conclusion could be strengthened by stating the significance of the findings more clearly. e.g.